Principles of economics - Henderson, J. Vernon (Massachussets : D.C. Health and Company, 1991)
There is no shortage of introductory economics texts, but there is a shortage of modern, relevant, and well-written ones. We wrote this text so that students could have a pedagogically sound presentation of modern economics.